Analysis distribution and segmentation of micro, small, and medium enterprises (MSMEs) in Kediri Residency Area: implications for local economic development - Qonitatul Hasanah; Inggrid Yanuar Risca Pratiwi; Zakiyah Amalia; Riska Nur Wakidah (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2023)
Micro, Small, and Medium Enterprises (MSMEs) are critical drivers of economic growth, especially in developing nations like Indonesia. This study focuses on the specific case of Kediri Residency, using 2018 data from the Central Bureau of Statistics of East Java Province to uncover insights for sustainable local economic development. Our methodology involved data acquisition, parsing, mining, filtering, and representation/ interaction. This process yielded a dataset of 168 data points, providing a nuanced view of MSMEs in Kediri Residency. Our analysis highlighted significant trends. Kediri Regency, for example, excelled in the Food and Beverage Industry (270 MSMEs) and Wood Industry (260 MSMEs). Blitar Regency thrived in the Wood Industry (235 MSMEs) and the Food and Beverage Industry (230 MSMEs). Tulungagung Regency showed strength in the Wood Industry (219 MSMEs). These findings have strategic implications for local economic development, such as sectoral strengthening, enhancing competitiveness, forming business clusters, and tailoring policies to MSMEs' unique needs. Comparing Kediri City to Kediri Regency and Blitar City to Blitar Regency revealed disparities and opportunities, highlighting the role of local policies and infrastructure in MSME development. In conclusion, our research provides actionable insights to formulate policies, develop infrastructure, improve financing access, and enhance skills training programs. These actions will catalyze MSME growth, promoting regional economic development and stability.